Effect of Physicochemical Characteristics of Soil on Population Density of Arbuscular Mycorrhizal Fungi in the Roots of Grapevine in Urmia - A. Mahdavi Bileh Savar; V. Sarvi Moghanloo; F. Mahdavi Bileh Savar (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2015)
Relationship of is one of the most useful interactions in terrestrial ecosystems that its positive effects on growth, physiology and ecology of different plants has been documented. This study investigated the relationship between important physicochemical characteristics of soils such as pH, electrical conductivity (EC), soil texture, organic carbon percentage, soil potassium percentage and the amount of accessible phosphorus with population of mycorrhizal fungi. After dividing the study region into four areas, 43 samples of soil were collected. The results of statistical analysis on physico-chemical characteristics of soil and their relation with population density of spores of arbuscular mycorrhizal fungi showed that there was a negative correlation between electrical conductivity (EC), pH, clay percent, and percent of soil available phosphorus, potassium percent, and percentage of organic carbon with the mean number of fungi. There were positive correlations between silt and sand percentages and mean number of spores present in the soil. Based on the coefficien of determination and based on study conditions, the best model for the rhizosphere was found tobe the one in wich available phosphorus percent of soil was the independent variable, and mean population of fungi as the dependant variable. The correlation between available phosphorus percent in soil samples with average fungi population density negative (P<0/05), but there was not a meaningful correlation between other traits and population density of fungi